2020
DOI: 10.1038/s41467-020-17378-z
|View full text |Cite|
|
Sign up to set email alerts
|

Mutations in COMP cause familial carpal tunnel syndrome

Abstract: Carpal tunnel syndrome (CTS) is the most common peripheral nerve entrapment syndrome, affecting a large proportion of the general population. Genetic susceptibility has been implicated in CTS, but the causative genes remain elusive. Here, we report the identification of two mutations in cartilage oligomeric matrix protein (COMP) that segregate with CTS in two large families with or without multiple epiphyseal dysplasia (MED). Both mutations impair the secretion of COMP by tenocytes, but the mutation associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Li et al also revealed the critical roles of ECM proteins in the cellular stress response in the pathogenesis of CTS with identification of two causative mutations in cartilage oligomeric matrix protein (COMP) [45]. The genetic predisposition to CTS development is suspected with: early onset of CTS in young individuals, repeated disease ocurrence in the same family as well as an increased incidence of CTS in relatives than in the general population.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Li et al also revealed the critical roles of ECM proteins in the cellular stress response in the pathogenesis of CTS with identification of two causative mutations in cartilage oligomeric matrix protein (COMP) [45]. The genetic predisposition to CTS development is suspected with: early onset of CTS in young individuals, repeated disease ocurrence in the same family as well as an increased incidence of CTS in relatives than in the general population.…”
Section: Pathophysiologymentioning
confidence: 99%
“…WES was performed for all recruited patients with congenital hemivertebrae and participating family members by Novogene Co, Ltd. (Hong Kong, China), using the Agilent SureSelect Human All Exon Kit on the Illumina sequencing platform. The WES data were processed as described previously [20]. The raw sequence data were first analyzed by fastp for quality control and filtering [21].…”
Section: Whole-exome Sequencing (Wes) and Copy Number Variations (Cnvs) Callingmentioning
confidence: 99%
“…Few studies have reported that on a genetic level there are at least 16 susceptible loci for CTS, and most of these genes are expressed in the aponeuroses [ 10 ]. The involved mechanism is reportedly involved the damage of tendon cells to cartilage oligomeric matrix protein secretion [ 11 ]; however, insufficient evidence is available to support the above-mentioned theory. Concurrently, the occurrence of CTS has been confirmed to be significantly associated with the incidence of heart diseases.…”
Section: Introductionmentioning
confidence: 99%